The Role of Self-Awareness in the Academic Procrastination of FPIP Students at Muhammadiyah Sidoarjo University - Azzahra, Fathimah; Ghozali Rusyid Affandi (Universitas Nahdatul Ulama Surabaya, 2024)
This research was carried out because of the phenomenon of many students doing academic procrastination. This research aims to find out the role of self-awareness against academic procrastination in FPIP students of Muhammadiyah University Sidoarjo. The method used in this research is quantitative correlation. The data collection technique in this study uses nonprobability sampling with purposive samplings. The population of this study is 4097 students with a sample of 365 students. The data collection technique uses the likert scale, the academic procrastination scale and the self-awareness scale. The data analysis technique uses simple linear regression with the help of JASP 0.16.4.0. Data analysis uses simple regression analysis which shows the result F = 96.789 with a significance < 0,001. The results reveal that there is an influence of self-awareness on academic procrastination of 24.8%.